Study of Potential and Real Seed Producing Capacity in Some Romanian Varieties of Legumes and Perennial Gramineae - Neculai Dragomir (Scientific Papers Animal Science and Biotechnologies, 2010)
This work presents the potential and real seed producing capacity in some Romanian varieties of legumes and perennial gramineae: Trifolium repens, Lotus corniculatus, Lolium perenne, Festuca pratensis, Festuca arundinacea and Dactylis glomerata. To calculate the potential production, we performed determinations and analyses on each variety, regarding floral apparatus’ morphological and anatomic structure (number of inflorescences, number of flowers, number of ovules/ovary), and the real production was determined „in situ”.